$latex 5s^{2} 5px^{2} (5d+6s) $ configurations in triply ionized xenon (Xe IV) - Reyna Almandos, Jorge Guillermo (1991)
The spectrum of triply ionized xenon (Xe IV) has been observed in the region 570-6900 Å The configurations $latex 5s^{2} 5p^{2} 5d $ and $latex 5s^{2} 5p^{2} 6s $ have been studied and the energy levels reported for these configurations by Moore [Atomic Energy Levels, Natl. Bur. Stand. Ref. Data Ser., Natl. Bur. Stand. (U.S.) Circ. No. 467 (U.S. GPO, Washington, D.C., 1971)] were revised and extended to include seven new levels. The configuration $latex 5s 5p^{4}$ was included in the analysis to take into account the strong interaction between this configuration and $latex 5s^{2} 5p^{2} 5d$. Configuration-interaction Rydberg series have been also included in the calculations. This investigation was supported by Hartree- Fock calculations.